2022
DOI: 10.3389/fnagi.2021.786322
|View full text |Cite
|
Sign up to set email alerts
|

Unique Phenotypes With Corresponding Pathology in Late-Onset Hereditary Transthyretin Amyloidosis of A97S vs. V30M

Abstract: ObjectiveHereditary transthyretin amyloidosis (ATTRv) encompasses different phenotypes among various genotypes. The analysis of the natural history and risk factors of faster progression in different genotypes would refine the treatment strategy.MethodsThe clinical manifestations of ATTRv from A97S (p.A117S) of Taiwanese and late-onset V30M (p.V50M) of Japanese were compared. An autopsy study of A97S was performed.ResultsThere existed three unique features in the A97S cohort compared to the V30M cohort: (1) dy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…In contrast to the most common TTR p. V50M mutation in western countries and Japan, 13 p. A117S mutation constitutes the majority of late‐onset ATTRv‐PN with cardiomyopathy in Taiwan and has also been reported in China and Southeast Asia 14–17 . Our recent report comparing the manifestations in patients with p. A117S and late‐onset p. V50M showed comparable clinical phenotypes and disease progression, and heart failure or sudden death due to cardiac amyloidosis was the predominant cause of death in both groups of patients 18 . In the present study, we combined echocardiography, CMR, and 99m Tc PYP scans to explore cardiac involvement in late‐onset ATTRv‐PN with predominant p. A117S genotype, which is invariantly associated with cardiomyopathy during the disease course 18,19 .…”
Section: Introductionmentioning
confidence: 62%
See 4 more Smart Citations
“…In contrast to the most common TTR p. V50M mutation in western countries and Japan, 13 p. A117S mutation constitutes the majority of late‐onset ATTRv‐PN with cardiomyopathy in Taiwan and has also been reported in China and Southeast Asia 14–17 . Our recent report comparing the manifestations in patients with p. A117S and late‐onset p. V50M showed comparable clinical phenotypes and disease progression, and heart failure or sudden death due to cardiac amyloidosis was the predominant cause of death in both groups of patients 18 . In the present study, we combined echocardiography, CMR, and 99m Tc PYP scans to explore cardiac involvement in late‐onset ATTRv‐PN with predominant p. A117S genotype, which is invariantly associated with cardiomyopathy during the disease course 18,19 .…”
Section: Introductionmentioning
confidence: 62%
“…The present study investigated the cardiomyopathic changes and their clinical and neuropathic associations in late‐onset ATTRv‐PN patients, the majority of whom were p. A117S mutant, which shared a similar phenotype to p. V50M mutant. 18 The important findings included (1) all the enrolled late‐onset ATTRv‐PN patients with various stages of severity consistently manifested cardiomyopathy as shown by significant radiotracer uptake on 99m Tc‐PYP SPECT imaging, (2) the cardiomyopathy was associated with compromised cardiac functional capacity (NYHA class I–III), significantly thicker IVSd on echocardiography; higher ECV, longer myocardial native T1, increased LVMi, and higher MVR on CMR, and elevated pro‐BNP in the blood, (3) the abnormal CMR parameters and elevated pro‐BNP level were associated with higher clinical stage, lower quality of life, more severe disability, and more autonomic dysfunction, and (4) there were significant correlations between the CMR biomarkers of cardiomyopathy and pathophysiological parameters of polyneuropathy. These findings suggested that cardiomyopathy is highly prevalent, related to neuropathic changes in both small‐ and larger‐fiber nerves and can reflect the overall severity and functional deficits in late late‐onset ATTRv‐PN patients.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations